Penilaian Kognitif Risiko Produksi Petani Berbasis Dikotomi Kendali Stoikisme - Ashiffa Maulana Erfandi; Mastur el; Epsi Euriga (Universitas Sebelas Maret, 2026)
Agriculture is a primary sector in human life that continuously faces dynamic changes and uncertainty in its development. Such uncertainty includes farming risks encountered by farmers, particularly production risks such as pest and disease attacks on agricultural land. Farmers possess experiential knowledge and philosophical values in assessing production risks; however, these assessments are often not yet reflective and lack sustained impact. This study aims to examine the primary and secondary cognitive appraisals of members of the Bimo Karyo Farmer Group, as well as the internalization of the Stoic principle of the dichotomy of control in preventive and mitigative actions in dealing with production risks. The research employed a descriptive qualitative method, using depth interviews with seven informants and data analysis techniques through coding (open, axial, and selective coding). The results indicate that most farmers demonstrate a negative primary appraisal (perceiving risk as a threat), as asynchronous planting patterns and seasonal influences increase the intensity of pest and disease attacks. In their secondary appraisal, farmers tend to adopt preventive measures, such as optimizing technical production practices, implementing crop rotation, and utilizing high-quality agricultural inputs. These findings reflect the Stoic value of the dichotomy of control, in which farmers are able to distinguish and focus on aspects within their control, while accepting—along with efforts to minimize—those beyond their control. Stakeholders are therefore encouraged to consider the psychological and philosophical dimensions of farmers, as these aspects shape their attitudes in organizing themselves within farmer groups.